Peranan Hukum Pajak sebagai Sumber Keuangan Negara pada Pembangunan Nasional dalam Upaya Mewujudkan Kesejahteraan Rakyat - Fatma Ulfatun Najicha (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The purpose of this paper is to determine the condition of the problems of public welfare in Indonesia and to determine the role of tax law as an effort to improve the welfare of the Indonesian people as a cost for national development. This paper uses a descriptive normative legal research method. The technique of tracing legal materials uses document study techniques, and analysis of studies using qualitative analysis. The result of this research is that improving people's welfare is the essence of national development. However, due to the COVID-19 pandemic in the last two years, the level of public welfare has decreased. Seeing the condition of the community's welfare level during the pandemic, it is necessary to have an instrument to improve and restore the Indonesian economy for development and public welfare. Taxes are an instrument of the Indonesian economy and are the main contribution of government revenues used for national development and state spending. Tax receipts in a pandemic situation have a role for economic recovery. From this condition, tax instruments can be prioritized for financing state spending, so that the state can overcome the problem of budget deficits, increase state spending, national development, and efforts to improve the welfare of the people so that people can feel the benefits of tax revenues for the construction of public service facilities and infrastructure, education. affordable, affordable health, defense and security, fuel subsidies, energy, and food orderly and smoothly.